The Kingdom of Siam - Carter, A. Cecil (G. P. Putnam s sons, 1904)
The royal family -- The government -- A general description of Siam -- Naval and military forces -- Siam from an historical standpoint -- Language of Siam -- Religion of Siam -- The capital -- Finance -- Currency and banking -- Agriculture -- Forestry -- Justice -- Education -- Archaeology -- Transportation and means of communication -- Mining -- Commerce -- The industries of Siam